2018
DOI: 10.1093/cid/ciy495
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Monotherapy May Be Insufficient to Treat Methicillin-resistantStaphylococcus aureusCoinfection in Children With Influenza-related Critical Illness

Abstract: Influenza-MRSA coinfection is associated with high fatality in critically ill children. These data support early addition of a second anti-MRSA antibiotic to vancomycin in suspected severe cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…This limitation is mitigated in part by the multicentric design and use of Monte Carlo cross validation methods. Second, bacterial coinfection is a known risk factor for more severe and sustained PARDS ( 21 ). However, we did not include coinfection in the predictive models because it is a difficult diagnosis to make prospectively at day 2 ( 21 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This limitation is mitigated in part by the multicentric design and use of Monte Carlo cross validation methods. Second, bacterial coinfection is a known risk factor for more severe and sustained PARDS ( 21 ). However, we did not include coinfection in the predictive models because it is a difficult diagnosis to make prospectively at day 2 ( 21 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, bacterial coinfection is a known risk factor for more severe and sustained PARDS ( 21 ). However, we did not include coinfection in the predictive models because it is a difficult diagnosis to make prospectively at day 2 ( 21 , 44 ). Third, the outcome was treated as a binary variable, without incorporating mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current data still lacks proof that the clinical presentation with viral-bacterial co-infections directly leads to worse outcomes, but a growing body of evidence suggests that influenza-bacterial co-infections are associated with higher morbidity and higher mortality [65,[73][74][75][76]. In fact, a recent study showed that the presence of co-infection in adults with influenza-associated acute respiratory syndrome requiring extra-corporeal membrane oxygenation was significantly associated with a fourfold increase in mortality [77], and another study in children with Staphylococcus aureus co-infection with influenza-related critical illness also showed a ninefold significant increase in mortality [78].…”
Section: Role Of Viral-bacterial Co-infections and Their Effect On Oumentioning
confidence: 99%
“…Linezolid therapy has been reported to produce a survival advantage in patients with nosocomial MRSA pneumonia (3,4). A recent study also suggested that vancomycin is insufficient to treat MRSA pneumonia in children with influenza-related critical illness (30). In animal studies, it has been shown that treatment with linezolid but not vancomycin significantly delayed weight loss compared with placebo during postinfluenza MRSA pneumonia (31).…”
Section: Discussionmentioning
confidence: 99%